Comparison of forearm angular momentum asymmetry and ipsilateral knee extension angular velocity coordination patterns in elite 100 m vs. 400 m sprinters - Gil, H.-J.; Lee, J.-H. (Korean Journal of Sport Biomechanics, 2025)
Objective: This study investigated differences in forearm angular momentum asymmetry and ipsilateral knee extension coordination between elite 100 m and 400 m sprinters to identify event-specific upper-lower limb coordination strategies. Method: Twelve elite collegiate sprinters (100 m: n = 7, 400 m: n = 5) performed maximum-velocity sprinting at 40 m. Three-dimensional kinematics were captured using markerless motion capture (10 cameras, 120 Hz). Forearm angular momentum was normalized to body mass, and ipsilateral coordination with knee extension angular velocity was quantified through cross-correlation analysis. Time lags (t peak) and maximum correlation coefficients (r max) were extracted to characterize temporal coupling patterns. Results: Dominant-side time lag differed significantly between groups (400 m: 45.24 ± 4.41 ms vs. 100 m: 26.71 ± 22.29 ms, p = .018, r_ES = -.656), with 400 m sprinters exhibiting 18.5 ms longer delays. Coordination strength showed a trend toward higher values in 400 m sprinters (p = .073) without reaching significance. No significant differences were found in angular momentum asymmetry or peak values between groups. Conclusion: Elite 100 m and 400 m sprinters demonstrated distinct temporal coordination strategies in dominant-side upper-lower limb coupling. The longer time lag in 400 m sprinters reflects energy-efficient coordination strategies, while shorter delays in 100 m sprinters prioritize rapid force production through tight temporal coupling. These findings indicate that temporal coordination patterns, rather than spatial asymmetry, serve as sensitive indicators of event-specific biomechanical adaptation, providing evidence-based foundations for individualized sprint training programs.